2021
DOI: 10.1098/rsfs.2020.0028
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for carbamate post-translational modification discovery and its application in Escherichia coli

Abstract: Carbon dioxide can influence cell phenotypes through the modulation of signalling pathways. CO 2 regulates cellular processes as diverse as metabolism, cellular homeostasis, chemosensing and pathogenesis. This diversity of regulated processes suggests a broadly conserved mechanism for CO 2 interactions with diverse cellular targets. CO 2 is generally unreactive but can interact with neutral amines on protein under normal intracellular cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although it has been reported that CO 2 -amine interactions on proteins can alter their physical and chemical properties, no attempts have been made to apply this as a synthetic method. 13 a ,25 We first investigated pentapeptide modification with FKVCF (Phe-Lys-Val-Cys-Phe) 26 with 1e under CO 2 and N 2 atmosphere. We detected conjugated product FKVCF- 1e after HPLC purification and by LC/MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been reported that CO 2 -amine interactions on proteins can alter their physical and chemical properties, no attempts have been made to apply this as a synthetic method. 13 a ,25 We first investigated pentapeptide modification with FKVCF (Phe-Lys-Val-Cys-Phe) 26 with 1e under CO 2 and N 2 atmosphere. We detected conjugated product FKVCF- 1e after HPLC purification and by LC/MS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…lipid-transfer protein (Lys-K65), Rubisco Large Subunit (Lys-185), Peroxidase (Lys-262 and Lys-268), FBA1 (Lys-293), eukaryotic aspartyl protease family protein (Lys-251), PSBQA (Lys-109), and Fe Superoxide dismutase 1 (Lys-208) (Linthwaite et al, 2018)). Similarly, a screen of an Escherichia coli lysates corresponding to 14% of the total proteome (294/4300 proteins) identified six CO 2 -binding sites (Linthwaite and Cann, 2021). In this instance, these included proteins involved in cellular processes identified as responsive to CO 2, i.e.…”
Section: Mass Spectrometry-based Approaches For Discovery Of Carbamat...mentioning
confidence: 99%
“…While many pathways are implicated as sensitive to changes in CO 2 , a discovery method is required to identify sites of CO 2 interaction within these pathways. Linthwaite & Cann [1] present research describing the use of state-of-the-art technology to discover CO 2 binding proteins within a soluble proteome and apply this methodology to Escherichia coli . This method has been previously deployed using the soluble leaf proteome of Arabidopsis thaliana with similar results: the discovery of a selection of proteins previously unknown to interact with CO 2 directly.…”
Section: Theme 1—carbon Dioxide Detection and Transportmentioning
confidence: 99%